Gestational vitamin D deficiency causes placental insufficiency and fetal intrauterine growth restriction partially through inducing placental inflammation. Issue 203 (October 2020) - Chen, Yuan Hua; Liu, Zhi Bing; Ma, Li; Zhang, Zhi Cheng; Fu, Lin; Yu, Zhen; Chen, Wei; Song, Ya Ping; Wang, Peng; Wang, Hua; Xu, De Xiang
Graphical abstract: Gestational vitamin D deficiency caused adverse birth outcomes, such as intrauterine growth restriction. Placental inflammation due to gestational vitamin D deficiency further impaired placental development and function. Thus, fetus cannot obtained sufficient nutrients and growth factors to support its growth. We propose that gestational vitamin D deficiency causes placental insufficiency and fetal intrauterine growth restriction partially through inducing placental inflammation. Highlights: Gestational VDD induces fetal IUGR. Gestational VDD inhibits placenta development. Gestational VDD impairs placental function. Gestational VDD is associated with increased inflammatory markers. NF-κB is activated in human placentas from mother with VDD. Abstract: Several epidemiological studies suggest an association between vitamin D deficiency (VDD) and fetal intrauterine growth restriction (IUGR). Here, we explored the mechanism through which VDD induced fetal IUGR. Pregnant mice were fed with VDD diet to establish VDD model. Cyp27b1 +/− mice were generated to develop a model of active vitamin D3 deficiency. Cyp27b1 +/− mice were injected with either 1α, 25(OH)2 D3 or vehicle once a day throughout pregnancy. As expected, fetal weight and crown-rump length were reduced in VDD diet-fed mice. Correspondingly, fetal weight and crown-rump length were lower in cyp27b1 +/− mice. 1α, 25(OH)2 D3 elevated fetal weight and crown-rump length, and protected cyp27b1 +/− mice from fetal IUGR. Further analysis found that placental proliferation was inhibited and placental weight was decreased in VDD diet-fed mice. Several growth factors and nutrient transfer pumps were downregulated in the placentas of VDD diet-fed mice. Mechanistically, several inflammatory cytokines were upregulated and placental NF-κB was activated not only in VDD diet-fed mice but also in VDD pregnant women. Interestingly, 1α, 25(OH)2 D3 inhibited the downregulated of placental nutrient transfer pumps and the upregulated of placental inflammatory cytokines in Cyp27b1+/- mice. These results provide experimental evidence that gestational VDD causes placental insufficiency and fetal IUGR may be through inducing placental inflammation.